Professional nurses' lived experiences regarding the performance management system in the Mopani district - Sheillah H. Mboweni; Lufuno Makhado (AOSIS, 2017)
Background: The purpose of the performance management system (PMS) is planning, monitoring, evaluation and development of employees to meet the organisational goals and objectives and transform of service delivery to excellence of the organisation. However, public services are deteriorating and implementation of PMS stimulated different views among professional nurses (PNs) in the Mopani district clinics, which warrants exploration and documentation of the findings. Objective: The objective of this study was to explore and describe the PNs' perceptions towards PMS. Methods: A qualitative, phenomenological research was conducted to explore and describe the nurses' lived experiences regarding PMS. A purposive sampling method was used. Data collection was done using focus group interviews. Three focus group discussion sessions were conducted, inclusive of six to nine participants in each session. Results: Twenty-two PNs were interviewed. The findings revealed the following themes: PNs' uncertainty regarding the implementation of PMS, poor implementation of PMS and its process, lack of knowledge and understanding of PMS implementation and its process, and negative attitudes towards the implementation of PMS. Conclusion: PNs perceived PMS negatively. There is a need to improve leadership and management behaviour by enhancing productivity, job satisfaction and organisational commitment. Constructive feedback, training and capacity development, including standardisation and stabilisation of performance instrument, might improve the process.